The effectiveness of melaleuca essential oil (Melaleuca Alternifolia Cheel) in the preventive control of diseases in bean cultivation (Revista de Ciências Agroveterinárias, 2024)
This study looks at the application of Melaleuca (Melaleuca alternifolia Cheel) essential oil to control diseases in bean crops. Considering the global and economic importance of the bean crop, the research investigated the potential of M. alternifolia, known as the tea tree, to suppress pathogens. In vitro tests were conducted, revealing that the essential oil (EO) inhibited the growth of fungi and bacteria from 0.5%. In vivo experiments, using a randomized statistical design, showed a significant reduction in the incidence and severity of diseases from 0.5%. The results suggest that Melaleuca EO can be an effective alternative for phytosanitary control of bean crops, highlighting its potential to promote sustainability and agricultural productivity.
Keywords: plant health; agricultural sustainability; integrated management; phytopathogenics; antimicrobial potential